2016
DOI: 10.1016/j.carpath.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

BRG1 and BRM SWI/SNF ATPases redundantly maintain cardiomyocyte homeostasis by regulating cardiomyocyte mitophagy and mitochondrial dynamics in vivo

Abstract: There has been an increasing recognition that mitochondrial perturbations play a central role in human heart failure. Discovery of mitochondrial networks, whose function is to maintain the regulation of mitochondrial biogenesis, autophagy (‘mitophagy’) and mitochondrial fusion/fission, are new potential therapeutic targets. Yet our understanding of how the molecular underpinning of these processes is just emerging. We recently identified a role of the SWI/SNF ATP-dependent chromatin remodeling complexes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 74 publications
(83 reference statements)
0
20
0
Order By: Relevance
“…We previously documented conditional loss of Brg1 in cardiomyocytes within 7 days of tamoxifen treatment in this model by PCR and IHC (Supplemental Fig. 1A–C) [11,12]. These mice (herein referred to as Brg1/Brm double mutants), which are null for BRG1 and BRM in cardiomyocytes, die at 6–22 days (mean of 11.6 ± 1.5 days) relative to the first day of tamoxifen treatment (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…We previously documented conditional loss of Brg1 in cardiomyocytes within 7 days of tamoxifen treatment in this model by PCR and IHC (Supplemental Fig. 1A–C) [11,12]. These mice (herein referred to as Brg1/Brm double mutants), which are null for BRG1 and BRM in cardiomyocytes, die at 6–22 days (mean of 11.6 ± 1.5 days) relative to the first day of tamoxifen treatment (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 90%
“…These mice (herein referred to as Brg1/Brm double mutants), which are null for BRG1 and BRM in cardiomyocytes, die at 6–22 days (mean of 11.6 ± 1.5 days) relative to the first day of tamoxifen treatment (Supplemental Fig. 1D) [12]. We have demonstrated that Brg1 conditional mutants on a wild-type background are viable, as are Brm −/− mice, indicating that the two catalytic subunits are functionally redundant in adult cardiomyocytes (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations